Pattern of contributing behaviors and their determinants among people living with HIV in Iran: A 30-year nationwide study - Gheibi, Zahra; Fararouei, Mohammad; Afrashteh, Sima; Akbari, Mojtaba; Afsar Kazerooni, Parvin; Shokoohi, Mostafa (Frontiers in Public Health, 2023)
A major shift in the routes of HIV transmission seams to be taking place in Iran. Our study aimed to investigate the 30-year trend of major HIV related behaviors in Iran. The national HIV/AIDS registry database (from September 1986 to July 2016 with data on 32,168 people newly diagnosed with HIV) was used to study the 30 years trend and demographic determinants of major HIV related behaviors. The highest rate of drug injection (DI) among people living with HIV (PLHIV) was reported during 1996 to 1999 (p-for trend <0.001) while the highest rate of sexual activity by minorities or hard to reach groups was during 2004 to 2011 (p-for trend <0.001). Among males, drug injection was directly associated with being single (ORsingle/married=1.34), being unemployed (ORunemployed/employed=1.94) and having lower level of education (OR